Comparison of Naive Bayes Method and Certainty Factor for Diagnosis of Preeclampsia - Wanti, Linda Perdana; Prasetya, Nur Wachid Adi; Sari, Laura; Puspitasari, Lina; Romadloni, Annisa (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 13 No 2 (2022): Vol. 13, No. 2 August 2022DO - 10.24843/LKJITI.2022.v13.i02.p04, 2022)
Preeclampsia is a disease often suffered by pregnant women caused by several factors such as a history of heredity, blood pressure, urine protein, and diabetes. The data sample used in this study is data on pregnant women in the 2020 time period recorded at health services in the former Cilacap Regency. This study was conducted to compare the final results of the Naive Bayes method and the certainty factor method in providing the results of a diagnosis of preeclampsia seen from the symptoms experienced by these pregnant women. The naïve Bayes approach provides decisions by managing statistical data and probabilities taken from the prediction of the likelihood of a pregnant woman showing symptoms of preeclampsia. Symptoms of preeclampsia, while the certainty factor method determines the certainty value of the diagnosis of preeclampsia in pregnant women based on the calculation of the CF value. The research output compares the two methods, showing that the certainty factor method provides more accurate diagnostic results than the Naive Bayes method. It happens because the CF method requires a minimum value of 0.2 and a maximum of 1 for each rule on the factors/symptoms involved, while the Naive Bayes method only requires values of 0 and 1 for each factor causing preeclampsia in pregnant women.